Kesiapan dan Tantangan Perusahaan Asuransi di Indonesia dalam Menerapkan PSAK 74 - Samuel Tirta Hartojo; Vena Purnamasari (Politeknik Ganesha Medan, 2023)
PSAK 74 is a new accounting standard in Indonesia that regulates Insurance Contracts and is the adoption of IFRS 17. Insurance companies need adjustments and can find obstacles when applying new accounting standards. The purpose of this study is to examine the readiness and challenges of insurance companies in Indonesia when implementing PSAK 74 before it is effective in 2025. The problem in this study is the readiness of insurance companies which includes understanding the scope, ability of Human Resources, Internal Control, Jobdesc Changes and infrastructure. technical. The second problem is the challenges of insurance companies which include data, systems, implementation processes, and display of financial statements. This study uses a survey method with data collection using a questionnaire. The data used in this study are the results of questionnaires to 59 insurance companies spread throughout Indonesia. Based on the research results, (1) insurance companies in Indonesia are ready to apply PSAK 74. (2) Insurance companies in Indonesia do not have challenges in implementing PSAK 74. The conclusion of this study is that when PSAK 74 is effectively implemented in 2025 it will not have a significant impact on insurance companies in Indonesia because every company has prepared things that support the implementation of PSAK 74 since before the initial implementation period, namely in 2023. Keywords: PSAK 74, Readiness, Challenges, IFRS 17, Insurance Companies.